Population Dynamics and Life History Response to Precipitation Changes for a Desert Ephemeral Plant With Biseasonal Germination - Mu, Xiao-Han; Huang, Gang; Li, Yan; Zheng, Xin-Jun; Xu, Gui-Qing; Wu, Xue; Wang, Yugang; Liu, Yan (Frontiers in Plant Science, 2021)
The changing availability of water resources and frequent extreme drought events in the context of global change will have a profound impact on desert vegetation, especially on herbaceous populations such as ephemerals. Erodium oxyrrhynchum is the dominant species in the Gurbantunggut Desert. It can germinate both in spring and autumn, which is important for herbaceous layer coverage and productivity. Therefore, we tracked and recorded the survival and reproduction of the E. oxyrrhynchum population under different precipitation treatments and established a population matrix model, monitored the allometry and leaf traits of the plants, and compared the performance of spring-germinating and autumn-germinating plants. Our results showed that: (1) the population dynamics were significantly affected by precipitation changes; (2) drought reduced the survival rate of the plants and accelerated the completion of their life history; (3) precipitation had a significant effect on seed production and growth rate, but not on plant height and allometry; (4) biomass, leaf area, specific leaf area, and hundred-grain weight of E. oxyrrhynchum also responded to changes in precipitation; (5) autumn-germinated plants had higher productivity, whereas spring-germinated plants exhibited higher reproductive efficiency, indicating that they had difference life history strategies. In conclusion, our results suggested that, although frequent or prolonged drought can significantly inhibit population growth, species with biseasonal germination are likely to be less affected.